Antimicrobial drug resistance and resistance factor transfer among Listeria species - Endang Purwati; Radu, Son; Hassan, Zaiton; Ghulam Rusul (Asian Fisheries Society, 1998)
Ninety four Listeria strains from salted fish samples were examined for resistance to 10 antibiotics and for the occurrence of plasmid DNA. Ten strains of L. ivanovii, three of L. denitrificans, two L. innocua and one L. seeligeri contained plasmid DNA ranging in size from 2.7 to 54 kilobases. Antibiotic susceptibility testingof the Listeria strains indicated that all were resistant to two or more antibiotics and that no isolates were resistant to gentamycin, norfloxacin and vancomycin. The incidence of antibiotic resistance was particularly high for L. onnocua, . dentrificans and L. welshimeri. On the other hand, L. ivanovii and L. monocytogenes exhibited the least resistance. In addition, a selected kanamycin resistant L. innocua strain was found to transfer kanamycin resistance with the concomitant transfer of a 54 kilobase plasmid to the recipients, tetracycline-resistant and kanamycin-sensitive L. innocua and L. monocytogenes strains (intra- and inter-species transfer), which suggested that dissemination of resistance to other strains of Listeria is likely.